The STUDY OF CORRELATION BETWEEN ELECTROLYTE IMBALANCE AND SEIZURES IN CRITICALLY ILL PATIENTS - AIZAZ FATIMA,; MOHAMMED IMRAN KHAN,; SURYA TIWARI, (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: A seizure is described as an episode of neurological malfunction brought on by aberrant neuronal activity that causes an abrupt alteration in behavior, motor function, and sensory perception. Electrolytes are a major factor in the occurrence of seizures. Seizures typically happen when there is a sudden change in the electrolyte concentration. In this study, the electrolyte imbalance pattern was evaluated, and the potential consequences of these diseases on seizure patients were investigated. Methods: This cross-sectional study involved 122 patients with new-onset focal or generalized seizures who were hospitalized in the medical wards and intensive care unit of Index Medical College, Hospital and Research Center. Those fulfilling inclusion and exclusion criteria were enrolled for thestudy and the blood samples were analyzed for sodium, potassium, calcium, and magnesium. Results: Generalized tonic-clonic seizure (GTCS) was the most common type of seizure observed in this study, which affected 90 (73.8%) of the 122 patients, the focal seizure affected 26 patients (21.3%), and status epilepticus affected six patients (4.9%). Out of 122 patients, 33 patients (27%) had electrolyte imbalances. The most common abnormality observed was hyponatremia, seen in 30 patients (91%). Hypocalcemia (3%), hypomagnesemia (3%), and hypokalemia (3%) were the other abnormalities noted. Hyponatremia is more common in GTCS, and a strong correlation between seizure type and blood sodium status was found. Conclusion: The study results showed a significant association between electrolyte imbalance and the first episode of seizures, the most common electrolyte abnormality being hyponatremia (p<0.001) followed by hypomagnesemia (p<0.023). Patients with metabolic causes of seizures were most frequently shown to have altered electrolytes among the other types of seizures.